3KO-NSCs ameliorate behavioral deficits and modulate gut microbiota in a VPA-induced C57BL/6 mouse model of autism - Wu, Caixia; Li, Xianjie; Wang, Han; Yang, Xiaoya; Liu, Zhaoming (Frontiers in Immunology, 2025)
BackgroundAutism spectrum disorder (ASD) involves complex neurological and gastrointestinal pathophysiology. Existing therapies rarely address the gut-brain axis connection. This study evaluated the therapeutic potential of immune-evasive human induced pluripotent stem cell-derived neural stem cells (3KO-NSCs) in a mouse model of ASD.MethodsWe used a valproic acid (VPA)-induced ASD model in C57BL/6 mice. Mice received systemic administration of 3KO-NSCs. Assessments included behavioral assays (social interaction, repetitive behaviors), hippocampal cytokine profiling (IL-6, TNF-α), 16S rRNA sequencing for gut microbiota analysis, immunohistochemistry (Iba1+ microglia), and ultrastructural synaptic analysis.Results3KO-hiPSC-NSC treatment significantly ameliorated VPA-induced ASD-like behaviors. It reduced hippocampal neuroinflammation (decreased IL-6 and TNF-α) and attenuated microglial overactivation (reduced Iba1+ cells), correcting synaptic pruning abnormalities. Concurrently, treatment restored gut microbiota diversity (increased Shannon index), enriching Bacteroides and reducing pro-inflammatory Proteobacteria.Conclusions3KO-NSCs exert dual therapeutic effects by mitigating central neuroinflammation and rebalancing gut microbiota. This provides the first direct evidence that stem cell therapy can modulate the gut-brain axis to treat ASD, positioning 3KO-NSCs as a novel bifunctional therapeutic strategy.